Mechanical properties of PLA-based composites for fused deposition modeling technology - Lebedev S. M. Sergey Mikhailovich; Gefle O. S. Olga Semenovna; Amitov E. T. Ernar Tanirbergenuly; Zhuravlev D. V. Denis Vladimirovich; Berchuk D. Yu. Denis Yurievich; Mikutsky E. A. Evgeny Aleksandrovich (2018, 2018)
Title screen